6+8t-3=6t+15-4t

Simple and best practice solution for 6+8t-3=6t+15-4t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+8t-3=6t+15-4t equation:


Simplifying
6 + 8t + -3 = 6t + 15 + -4t

Reorder the terms:
6 + -3 + 8t = 6t + 15 + -4t

Combine like terms: 6 + -3 = 3
3 + 8t = 6t + 15 + -4t

Reorder the terms:
3 + 8t = 15 + 6t + -4t

Combine like terms: 6t + -4t = 2t
3 + 8t = 15 + 2t

Solving
3 + 8t = 15 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
3 + 8t + -2t = 15 + 2t + -2t

Combine like terms: 8t + -2t = 6t
3 + 6t = 15 + 2t + -2t

Combine like terms: 2t + -2t = 0
3 + 6t = 15 + 0
3 + 6t = 15

Add '-3' to each side of the equation.
3 + -3 + 6t = 15 + -3

Combine like terms: 3 + -3 = 0
0 + 6t = 15 + -3
6t = 15 + -3

Combine like terms: 15 + -3 = 12
6t = 12

Divide each side by '6'.
t = 2

Simplifying
t = 2

See similar equations:

| 4x-3y=-28 | | 5/4-(1/8)x=11/3-(5/6)x | | y+5=15x+10 | | 2n+13n=75 | | 3(4x+5)+2x=22 | | -40=8n-8 | | 7500.00+155x=0 | | -7=v-6 | | -11/3-(5/6)x=-1/22+(5/6)x | | x^3-7x^2-17x-9= | | 3(4x-5)+8=-67 | | 3(x+2)=4+2(x-3) | | -4f+1=16 | | 16+3x=9x+22 | | 25x^3+10x^2+x= | | x*x*x+2x*x-5x= | | 3g+3(-5+5g)=1-g | | 3ln(X)+ln(24)=ln(3) | | -6(3)-20=-2(3)+4(1-3(3)) | | 3x+50=90 | | 2.7q-5.6-5.8q=-4.1q-2.1 | | 7x+3=5x-15 | | 3x-50=90 | | 3x-50=120 | | y=3x^2+9x-30 | | C+273.15=k | | 3x-8=2(x-4)+x | | 12-3x=o | | 16y=480 | | 20-93=8a+51 | | 5x-11=x-24 | | 5(2x-4)=10x-9 |

Equations solver categories